TINJAUAN PERENCANAAN DRAINASE JALAN RAYA SIMPANG EMPAT – AIR BALAM KABUPATEN PASAMAN BARAT - Ronal Afrian; Masril Masril; Ana Susanti Yusman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The problem of flooding or inundation often occurs on Indonesian roads, including on the Simpang Empat-Air Balam road, West Pasaman Regency. So that it annoys road users and causes damage to the pavement. Stagnant caused by a drainage system that is not optimal due to sedimentation in the curb inlet and in the side channel. So to find out how the drainage system is performing, a hydrological analysis is carried out to calculate the design discharge for a period of 10 years according to the drainage area and typology of the district and then compared with the discharge of the existing channel and culvert. The results of the comparison of the planned discharge and the existing discharge indicate that the side channel cannot accommodate the design discharge, so it is necessary to redesign the dimensions of the side and culvert. Keywords: hydrological analysis, design discharge, side dimension re-planning